2011
DOI: 10.1016/j.hedp.2011.05.001
|View full text |Cite
|
Sign up to set email alerts
|

A consistent approach for mixed detailed and statistical calculation of opacities in hot plasmas

Abstract: Absorption and emission spectra of plasmas with multicharged-ions contain transition arrays with a huge number of coalescent electricdipole (E1) lines, which are well suited for treatment by the unresolved transition array and derivative methods. But, some transition arrays show detailed features whose description requires diagonalization of the Hamiltonian matrix. We developed a hybrid opacity code, called SCORCG, which combines statistical approaches with fine-structure calculations consistently. Data requir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…Calculations of the free-free cross-section involve quantities related to the elastic-scattering matrix elements for electron-impact excitation of ions. The detailed (fine-structure) opacity code SCO-RCG [16][17][18] enables one to compute precise opacities for the calculation of accurate Rosseland means (see Section 3.2). The (super-)configurations are generated by the SCO code [19] on the basis of a statistical fluctuation theory (see the details below) and a self-consistent computation of atomic structure is performed for all the configurations.…”
Section: Radiative Opacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations of the free-free cross-section involve quantities related to the elastic-scattering matrix elements for electron-impact excitation of ions. The detailed (fine-structure) opacity code SCO-RCG [16][17][18] enables one to compute precise opacities for the calculation of accurate Rosseland means (see Section 3.2). The (super-)configurations are generated by the SCO code [19] on the basis of a statistical fluctuation theory (see the details below) and a self-consistent computation of atomic structure is performed for all the configurations.…”
Section: Radiative Opacitymentioning
confidence: 99%
“…As an example, the hydrogen H β profile computed by SCO-RCG at the conditions of Wiese et al is shown in Figure 24, right. For more complex ions, a cruder approach is used [16].…”
Section: Stark Broadening White Dwarfs and Balmer Linesmentioning
confidence: 99%
“…These methods were proposed to address the aforementioned issue in a pragmatic manner. In section 3, the detailed opacity code SCO-RCG [7,8] is briefly described. The statistical approach that is currently used in the code to model those Rydberg spectators is explained.…”
Section: Introductionmentioning
confidence: 99%
“…The recent experiment performed on the LULI2000 facility [4] aimed at checking a similar effect at fixed T but varying the atomic number Z: at T ∼ 20 eV, the 2p − 3d splitting is expected to vanish when Z decreases from 29 (Cu) to 26 (Fe). To describe this experiment, several models have been used and compared [5]: a statistical analysis with the superconfiguration code SCO [6], detailed-level accounting approaches using either HULLAC [7] or FAC [8] packages, the mixed approach SCO-RCG [9] combining the SCO approach with a detailed line analysis based on Cowan's code, and the collisional-radiative code SCRIC [10] suited to characterize the non-local-thermodynamic-equilibrium effects. It turned out that HULLAC a e-mail: michel.poirier@cea.fr This is an Open Access article distributed under the terms of the Creative Commons Attribution License 2.0, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.…”
Section: Introductionmentioning
confidence: 99%